O direito de ser ouvido no procedimento administrativo de fiscalização - Canhadas, Fernando Augusto Martins (2007)
The purpose of this paper was, by systematizing some doubts still unsolved by doctrine related to the guarantees applicable to the inspection administrative proceedings, to sustain the need of attempting to the private s right to be heard on such proceedings, as an indispensable mean in the search for the material truth that, to its turn, derives directly from the so called substantive conception of the due process of law. Our main concern was to pursue solid grounds for that conclusion. In this context, the first defiance was to draw up some conceptual delimitation about the formal and the material aspects of that constitutional clause, in view of the direct correspondence between the subject of the inspection proceedings and the issues regarding the freedom and the property limitations, since such proceedings involve administrative acts enacted under the so called police power. Afterwards we elaborated our conceptual differentiation between process and administrative proceedings, based upon our interpretation that the guarantees established on article 5, LV of the Brazilian Constitution, concerning to the right of full defense and the contradiction, are only applicable to the process itself, thus characterized by a litigation deriving from a conflict of interests. On the other side we verified that the guarantees related to the substantive due process of law, such as the principles of the equity, reasonability, proportionality and of the efficacy, shall remain in the proceedings not qualified by litigation. Further, we have developed the idea of the need for such inspection proceedings and not process to serve the search for the material truth and we concluded that such constitutional clause only can be accomplished by a deep investigation of the facts analyzed. Finally, we concluded that one of the indispensable means to the exercise of this search is the actually hearing the interested private. Thus, based on a theoretical construction aiming to solve several practical cases presented as illustration, we finalized our work asseverating that, although the guarantees of full defense and the contradiction are not applicable to all types of inspection administrative proceeding including those related to tax issues resides the duty of the State to hear the privates, in return to their right to be heard